Metamizole-induced agranulocytosis (MIA): a mini review - Markos K. Tomidis Chatzimanouil; Ines Goppelt; Yvonne Zeissig; Ulrich J. Sachs; Martin W. Laass (SpringerOpen, 2023)
Abstract Metamizole is an analgesic, antipyretic, and spasmolytic drug in Germany only approved for the treatment of severe pain or high fever that does not respond to other measures. In recent years, an increased use has been described among both adults and children, often against the approved indication. The most important side effect of metamizole is the development of agranulocytosis (neutrophil count < 500/µL). Incidence of metamizole-induced agranulocytosis (MIA) ranges depending on the study from 0.96 cases per million per year to 1:1602 per patient and metamizole prescription. The risk of agranulocytosis in children remains unclear, but is probably lower than in adults. Female gender and older age are associated with higher incidence, reflecting prescription distribution. MIA is dose-independent and risk seems to increase with duration of intake. In patients with past exposure, re-exposure may lead to rapid onset. MIA is believed to be induced either through immunologic or toxic mechanisms. MIA presents with fever, sore throat, fatigue, and mucosal inflammation, up to ulceration. Even in the case of suspected MIA, treatment with metamizole should be immediately paused and an examination of the blood cell count is required. In case of local or systemic infections, empirical therapy with broad-spectrum antibiotics should be administered. G-CSF therapy should be limited to patients with poor prognostic factors. The patient should be monitored closely until the neutrophil count returns to normal. Re-exposure to metamizole must be avoided.